2022
DOI: 10.1088/1755-1315/998/1/012028
|View full text |Cite
|
Sign up to set email alerts
|

Design and manufacture of polylacticacid (PLA) filament storage for 3-dimensional printing with composite material.

Abstract: 3-dimensional printing is an additive manufacturing (AM) method using polylacticacid (PLA) filaments. However, PLA filaments still have limitations such as the hygroscopic properties of the material. This type of filament easily absorbs air from air humidity, so it will have an impact on the chemical damage of PLA. In this research, a composite file storage area will be designed. The method of making this file storage area will use a composite material Medium Density Board (MDF) with a simple manufacturing met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Suharjanto et al reported that filament storage using medium-density boards prevents and reduces air absorption of PLA filament and filament life, leading to the maintenance of the printing system. Note that the accuracy after modeling varies depending on the storage method [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Suharjanto et al reported that filament storage using medium-density boards prevents and reduces air absorption of PLA filament and filament life, leading to the maintenance of the printing system. Note that the accuracy after modeling varies depending on the storage method [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“… 17 19 In terms of radiation attenuation, PLA is a suitable material due to its high atomic number and density, which makes it an effective radiation dose modulator. 20 22 However, it is important to note that PLA is not as flexible as TPU, so it may not be suitable for all applications. Another material option is acrylonitrile-butadiene-styrene (ABS), which has a density similar to that of PLA but is more flexible, making it suitable for certain applications.…”
Section: Methodsmentioning
confidence: 99%